Integrated Chinese Herbal Medicine Therapy Improves the Survival of Patients With Ovarian Cancer. (November 2019) - Chang, Cherry Yin-Yi; Yang, Pei-Yuu; Tsai, Fuu-Jen; Li, Te-Mao; Chiou, Jian-Shiun; Chen, Chao-Jung; Lin, Ting-Hsu; Liao, Chiu-Chu; Huang, Shao-Mei; Ban, Bo; Liang, Wen-Miin; Lin, Ying-Ju
Background: Ovarian cancer is the seventh most commonly diagnosed malignancy worldwide and has the highest mortality rate among all gynecological cancers. Chinese herbal medicine (CHM) is widely applied in Taiwan and has been used in integrated therapies to treat patients with cancer.Methods: Patients with ovarian cancer who were registered in the Taiwan Registry for Catastrophic Illness Patients Database between 1997 and 2012 were considered for this study. A 1:1 individual matching by age was implemented. A total of 101 CHM users and 101 non-CHM users were involved. A Cox proportional hazard regression model was applied to evaluate the hazard ratio of overall mortality. The Kaplan-Meier method and log-rank test were used to calculate the cumulative incidence of the overall survival rate. Association rule mining and network analysis were used to analyze CHM prescription patterns.Results: CHM users showed a significantly lower risk of overall mortality than nonusers (hazard ratio = 0.45, 95% confidence interval = 0.23-0.91; P = .0256; multivariate Cox proportional hazard model). The cumulative incidence of the overall survival probability was higher for CHM users than for non-CHM users (log-rank test, P = .0009). Association rule mining and network analysis suggested that the main CHM cluster was associated with the usage of Bu-Zhong-Yi-Qi-Tang, Chuan-Xiong, and Xi-Xin, followed by the use of Bai-Shao, Da-Huang, and Di-Huang.Conclusions: CHM, as an adjunctive therapy, may reduce the overall mortality in patients with ovarian cancer. A list of herbal medicines that could potentially be used in future studies and clinical trials has also been provided.